2019
DOI: 10.1038/s41467-019-08541-2
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological reactivation of MYC-dependent apoptosis induces susceptibility to anti-PD-1 immunotherapy

Abstract: Elevated MYC expression sensitizes tumor cells to apoptosis but the therapeutic potential of this mechanism remains unclear. We find, in a model of MYC-driven breast cancer, that pharmacological activation of AMPK strongly synergizes with BCL-2/BCL-XL inhibitors to activate apoptosis. We demonstrate the translational potential of an AMPK and BCL-2/BCL-XL co-targeting strategy in ex vivo and in vivo models of MYC-high breast cancer. Metformin combined with navitoclax or venetoclax efficiently inhibited tumor gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 59 publications
1
69
0
Order By: Relevance
“…73). Moreover, in a murine cancer model, venetoclax enhanced anti-PD-1-mediated T cell antitumor activity (73,74). In conclusion, the current study provides evidence that HIV reservoir-harboring cells have been selected for survivability, conferred, at least in part, through BCL-2.…”
Section: Discussionmentioning
confidence: 61%
“…73). Moreover, in a murine cancer model, venetoclax enhanced anti-PD-1-mediated T cell antitumor activity (73,74). In conclusion, the current study provides evidence that HIV reservoir-harboring cells have been selected for survivability, conferred, at least in part, through BCL-2.…”
Section: Discussionmentioning
confidence: 61%
“…84 Such translational potential of metformin to convert immunotherapy-resistant patients into those showing clinical benefit has been supported by the discovery that adjuvant metformin plus anti-PD-1 treatment results in durable antitumor responses by preventing the presentation of PD-1 + / CD8 + T-cell infiltrates after drug withdrawal. 85 A retrospective cohort study including patients diagnosed with metastatic malignant melanoma and treated with anti-PD-1 only or anti-CTLA4/ anti-PD-1 combination therapies, with or without metformin, revealed favorable treatment-related outcomes in terms of objective response rate, disease control rate, overall survival, and progression-free survival in patients who have received metformin in combination with immune-checkpoint inhibitors, albeit without reaching statistical significance likely due to the small sample size. 86 An analysis of the immunomodulatory effects of metformin in a clinical trial of head and neck squamous cell carcinoma revealed its ability to increase both CD8 + effector T-cells and FoxP3 + T reg cell infiltrates in the TME.…”
Section: Clinical Efficacy and Ongoing Trials Of Metformin Combined Wmentioning
confidence: 99%
“…To obtain additive or synergistic effects, enhance efficacy of treatment and combat genetically heterogeneous cancers, Bcl-2 inhibitors were combined with other anticancer drugs ( Fig. S1c; bcl2icombi.info) (Chen, Jin et al, 2011, Haikala, Anttila et al, 2019, Jeong, Oh et al, 2019, Shen, Li et al, 2018. The drug combinations were also used to lower the dose of Bcl-2 inhibitors to overcome resistance and toxicity issues for non-malignant cells (Adams et al, 2018).…”
Section: Introductionmentioning
confidence: 99%